PERSEPSI SISWA TERHADAP PEMBELAJARAN SENI TARI DI SMA NEGERI I WAY TENONG - Fitri Sawalena; Agung Kurniawan; Iqbal Hilal (Jurnal Seni dan Pembelajaran, 2013)
The objective of this research was to describe the students’ perceptions to dancing art learning at Senior High. School 1 in Way Tenong.This research used descriptive method. Data sources were seven Grade X female students joining dancing art self-development. Data were collected with observation of art learning process and interviews to explore. Students’ perceptions on dancing learning. Questions included students’ perceptions on the initial, core, and closing activities of learning process. Documentation in forms of pictures and filed notes were conducted by teachers and students.The results showed that dancing learning in SMA N11 Way Tenong was good to be seen from initial, core, and closing activities at the learning process. The interview results showed that most students expressed that the learning process was good, however, some students suggested that there. were some drawbacks at the learning process.Penelitian ini bertujuan untuk mendeskripsikan. Kegiatan guru dalam pembelajaran tari sigeh penguten, aktivitas siswa, dan persepsi siswa terhadap pembelajaran seni tari di SMA Negeri 1 Way Tenong. Metode penelitian ini adalah metode deskriptif kualitatif. Sumber data dalam penelitian ini adalah siswa perempuan kelas X yang mengikuti pengembangan diri seni tari sebanyak tujuh orang. Teknik pengumpulan data yang digunakan observasi proses pembelajaran tari, wawancara. dokumentasi. Pembelajran seni tari sudah baik dilihat dari kegiatan awal, inti dan penutup saat proses pembelajaran. Dari hasil wawancara kepada siswa tentang persepsi terhadap pembelajaran seni tari, sebagian besar siswa mengungkapkan bahwa proses pembelajaran sudah baik namun ada sebagian siswa berpendapat masih terdapat beberapa kekurangan pada saat proses pembelajaran berlangsung.Kata kunci : pendidikan, persepsi, pembelajaran tari